In vitro study of CD133 human stem cells labeled with superparamagnetic iron oxide nanoparticles - Gamarra, L. F.; Pavon, L. F.; Marti, L. C.; Pontuschka, W. M.; Mamani, J. B.; Carneiro, S. M.; Camargo-Mathias, M. I. [UNESP]; Moreira-Filho, C. A.; Amaro, E. (Elsevier B.V., 2008)
Superparamagnetic iron oxide nanoparticles (SPIONs) are applied in stem cell labeling because of their high magnetic susceptibility as compared with ordinary paramagnetic species, their low toxicity, and their ease of magnetic manipulation. The present work is the study of CD133(+) stem cell labeling by SPIONs coupled to a specific antibody (AC133), resulting in the antigenic labeling of the CD133+ stem cell, and a method was developed for the quantification of the SPION content per cell, necessary for molecular imaging optimization. Flow cytometry analysis established the efficiency of the selection process and helped determine that the CD133 cells selected by chromatographic affinity express the transmembrane glycoprotein CD133. The presence of antibodies coupled to the SPION, expressed in the cell membrane, was observed by transmission electron microscopy. Quantification of the SPION concentration in the marked cells using the ferromagnetic resonance technique resulted in a value of 1.70 x 10 (13) mol iron (9.5 pg) or 7.0 x 10 (6) nanoparticles per cell ( the measurement was carried out in a volume of 2 mu L containing about 6.16 x 10 5 pg iron, equivalent to 4.5 x 10 (11) SPIONs). (c) 2008 Elsevier B.V. All rights reserved.
Keywords: Cell labeling; Molecular imaging; Ferromagnetic resonance; CD133; SPIONs